2019
DOI: 10.1002/humu.23965
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive profiling of BRCA1 and BRCA2 variants in breast and ovarian cancer in Chinese patients

Abstract: The identification and interpretation of germline BRCA1/2 variants become increasingly important in breast and ovarian cancer (OC) treatment. However, there is no comprehensive analysis of the germline BRCA1/2 variants in a Chinese population. Here we performed a systematic review and meta-analysis on such variants from 94 publications. A total of 2,128 BRCA1/2 variant records were extracted, including 601 from BRCA1 and 632 from BRCA2. In addition, 414, 734, 449, and 307 variants were also recorded in the BIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 36 publications
(40 reference statements)
1
22
0
Order By: Relevance
“…These differences may originate from the selection of subjects and the database used for analysis. As addressed in a recently published meta-analysis (47), the variant profile in ethnically Chinese people was distinctive from those in other ethnic groups with no distinct founder pathogenic variants. However, this conclusion should be treated cautiously.…”
Section: Discussionmentioning
confidence: 93%
“…These differences may originate from the selection of subjects and the database used for analysis. As addressed in a recently published meta-analysis (47), the variant profile in ethnically Chinese people was distinctive from those in other ethnic groups with no distinct founder pathogenic variants. However, this conclusion should be treated cautiously.…”
Section: Discussionmentioning
confidence: 93%
“…To date, several studies have reported the BRCA1/2 pathogenic variants from breast or ovarian cancer in Chinese populations with diverse results. A meta-analysis collected 94 publications with 2128 BRCA1/2 variant records which showed several high-frequency variants but no potential founder variants were identified [26], for example, the two highest recurrent variants c.5470_5477delATTGGGCA [27][28][29] in BRCA1 and c.3109C>T in BRCA2 [25,30].…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have reported the BRCA1/2 pathogenic variants from breast or ovarian cancer in Chinese populations with diverse results. A meta-analysis collected 94 publications with 2128 BRCA1/2 variant records which showed several high-frequency variants but no potential founder variants were identified [ 26 ], for example, the two highest recurrent variants c.5470_5477delATTGGGCA [ 27 29 ] in BRCA1 and c.3109C>T in BRCA2 [ 25 , 30 ]. Recently, You et al identified five recurrent variants in 172 Chinese women with epithelial ovarian cancer, including three pathogenic mutations ( BRCA1 c.5470_5477delATTGGGCA and c.66dup and BRCA2 c.1963delC) and two VUS missense mutations ( BRCA2 c.1568A>G and c.6325G>A) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that pathogenic germline mutations increase the risk of cancers, including not only CRC 7 but also hereditary breast and ovarian cancer syndrome 9 and lung cancer 10 . However, this risk remains to be clearly defined for Chinese patients with CRC.…”
Section: Introductionmentioning
confidence: 99%